Repurposing Disulfiram as an Antimicrobial Agent in Topical Infections - Maria Lajarin-Reinares; Eloy Pena-Rodríguez; Mariona Cañellas-Santos; Elisabet Rosell-Vives; Pilar Cortés; Montserrat Llagostera Casas; Maria Àngels Calvo; Francisco Fernandez-Campos (MDPI AG, 2022)
Antimicrobial drugs applied topically offer several advantages. However, the widespread use of antibiotics has led to increasing antimicrobial resistance. One interesting approach in the drug discovery process is drug repurposing. Disulfiram, which was originally approved as an anti-alcoholism drug, offers an attractive alternative to treat topical multidrug resistance bacteria in skin human infections. This study aimed to evaluate the biopharmaceutical characteristics of the drug and the effects arising from its topical application in detail. Microdilution susceptibility testing showed antibacterial activity against Gram-positive bacteria Staphylococcus aureus and Streptococcus pyogenes. Dermal absorption revealed no permeation in pig skin. The quantification of the drug retained in pig skin demonstrated concentrations in the stratum corneum and epidermis, enough to treat skin infections. Moreover, in vitro cytotoxicity and micro-array analyses were performed to better understand the mechanism of action and revealed the importance of the drug as a metal ion chelator. Together, our findings suggest that disulfiram has the potential to be repurposed as an effective antibiotic to treat superficial human skin infections.